Framing Conflict in Political Discourse: Positive and Negative Politeness of Bassem Youssef and Piers Morgan’s Debate - AuliaPutri, Adinda Nurul; Mansyur, Agus Salim; Abqoriyyah, Fourus Huznatul (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2025)
This study examines the positive and negative politeness strategies employed by Bassem Youssef and Piers Morgan in their discussion of the Israel-Hamas conflict in the YouTube video Wouldn’t You Resist? Bassem Youssef Returns for More on the Israel-Hamas War. Using Brown and Levinson’s (1987) politeness theory, this research explores how linguistic strategies manage face-threatening acts and influence audience perceptions. A qualitative descriptive approach is applied to analyze textual and contextual factors. Findings reveal that both speakers utilize various politeness strategies such as exaggeration, seeking agreement, and hedging to build rapport, mitigate conflict, and maintain discourse balance. This study highlights the significance of politeness in shaping political communication and fostering constructive discussions.